PENDEKATAN ARSITEKTUR METAFORA PADA PERANCANGAN STADION AKUATIK DELI SPORT CITY - Matondang, Rifky Rahmansyah; Rambe, Yunita Syafitri; Suprayitno (Indonesian Society of Applied Science, 2024)
North Sumatra Province is set to host the 21st National Sports Week again, one of the sports buildings to be built is the Stadium for Aquatic Sports. This design approach is Metaphor architecture. This is to give the identity of the building. Planning principles by taking the formation of swimmers and water. The purpose of this study is to assess the success of the Aquatic Stadium building design with the application of international standards using the Metaphor Architecture Concept. The design focuses on the theme that has been determined and is included in the arrangement of aquatic sports arenas and other supporting facilities. The concept in this design is through the process of finding ideas about architectural data on the Aquatic Stadium from various sources of information. The research method is carried out by analysing and conceptualising the availability of data, and conducting a validation test of the design results with the metaphorical indicators used in planning. The result of this research is that it has followed the standards and the indicators given are in accordance with the design. The results of the research can be used as a building identity for the Deli Sport Centre area. Later this suitability, can be used as an output as a planning that provides regional identity.